Prompting Children’s Belief Revision About Balance Through Primary and Secondary Sources of Evidence - Larsen, Nicole E.; Venkadasalam, Vaunam P.; Ganea, Patricia A. (Frontiers in Psychology, 2020)
Children’s understanding of how to balance objects on a beam has been studied extensively over the last 50 years. This body of research has shown that children’s beliefs about balance evolve through stages, going from a stage where children lack a consistent theory (No Theory), to becoming Center Theorists at around age 6 (believing that all objects balance in their geometric centre) to Mass Theorists at around age 8 when they begin to consider the distribution of objects’ mass. The current study explored whether children have a larger range of levels of understanding in balance relations. Most of the research on balance relations with children has been conducted using a single object, weighted either proportionally or disproportionally on either side. Instead of using a single object, 5-year-olds (N = 102, Age = 5.49) were shown 4 pairs of objects, two with the same weight and two with different weight. By pairing multiple objects of same or different weight, we gave children the opportunity to make judgments about multiple individual objects placed on the scale. Children were told to place the object pairs on a beam where they thought the objects would balance. We found evidence for an intermediate category of understanding: transition theorists. These transition theorists represent children who have two distinct theories, one for how to balance same weight objects, and one for how to balance different weight objects, but one of these theories was incorrect. Following the assessment of children’s understanding of balance, we used different sources of evidence to teach children the correct Mass Theory. Specifically, we compared children’s learning from evidence that was either presented through primary sources (a guided activity) or secondary sources (picture books). We then post-tested their understanding of balance using the same measure. Results show children learn about balance equally from both primary and secondary sources. Findings are discussed in terms of theoretical and practical implications.